Advances in the Rehabilitation of the Spinal Cord–Injured Patient: The Orthopaedic Surgeons' Perspective. Issue 21 (1st November 2019) - Kwon, Brian K.; Banaszek, Dan; Kirshblum, Steven
Abstract : Acute traumatic spinal cord injury is a devastating condition affecting 17, 700 new patients per year in the United States alone. Typically, orthopaedic surgeons focus on managing the acute surgical aspects of care (eg, surgical spinal decompression and stabilization). However, in the care of these patients, being familiar with how to prognosticate neurologic recovery and manage secondary complications is extremely important. In addition, as an integral part of the multidisciplinary care team, the surgeon should have an awareness of contemporary rehabilitation approaches to maximize function and facilitate reintegration into the community. The purpose of this review article is to provide a surgeon's perspective on these aspects of spinal cord injury care.